Coaxial Electrospun Nanofibers as Pharmaceutical Nanoformulation for Controlled Drug Release - Amiruddin, Fadzli Zaini; Balu, Ranganathan; Subramaniam , Sundarrajan; Seeram , Ramakrishna (2014)
Pharmaceutical nanoformulations for controlled drug release, caters to the need of targeted delivery thereby minimizing the side effects and the economics of the drug regimen costing. Electrospinning produces nanofibers which has enormous application for diversified usage in healthcare, green technology, filtration and military aids. Organic polymeric nanofibers are used for healthcare applications. FDA approved organic polymers, PCL, PLLA and block copolymer PLLA-CL were used for the fabrication of nanofibers for controlled drug release. Coaxial nanofibers were produced with protein molecules embedded in the core structure and FDA approved organic polymer in the shell structure protecting the highly labile protein molecules from denaturation. Bovine Serum Albumin (BSA), Lysozyme and IgG are the protein mixture embedded in the core structure. Different concentrations of polymeric material of PCL, PLLA and block copolymer PLLA-CL were used in the range of 10–18% (W/V). The solvents used were highly evaporable with approved residual levels presence in the nanofibers scaffolds.